KONSEP PENDIDIKAN PROFETIK BERBASIS EDUTAINMENT PERSPEKTIF YUSUF QARADHAWI - Muhammad Taufan Khasani (Conciencia, 2015)
This research is a motivated rampant reality educational process that tends not to appreciate humanity (read: nature) learners. The students are forced to learn the material in the pile of the stiff and tense atmosphere. As a prolific scholar, preachers, and education practitioners, Yusuf Qaradawi offers a prophetic character of the concept of education (according to the spirit and the prophetic mission) and humanist scattered in various works. The approach is sticking to the principles of Islam which provide convenience (Taysir). Such an approach, later known as edutainment. Unfortunately, the ideas of education that students appreciate nature has not been widely applied in the learning process in educational institutions of Islam. Therefore, this study aims to determine the nature and characteristics of the prophetic education Qaradhawi based edutainment and its relevance to other educational concepts. The primary data source in this study a variety of texts Yusuf Qaradawi and other relevant texts as secondary data. This research type literature (library research), data collection using the documentation techniques. Data analysis techniques used in the form of qualitative descriptive analysis. Because this study examines the thought leaders, the content analysis technique was used. From the analysis, it was found: (1). In essence, education to the spirit and the prophetic mission (read: prophetic education) is part of the effort to prepare students for the teachings of Islam in their lives properly. Thus, Islamic education is a part of Islamic da'wah should provide ease and convenience to students. The implication, as the prophetic educational purposes in line with the objectives of Islamic law (shari'a maqashid); (2). edutainment-based education characteristic prophetic form: the aim of liberating learners of oppression, the approach nature, a process that involves learners actively, integrative curriculum, competent educators and learners developed in accordance with the nature of humanity; (3). The concept of edutainment-based prophetic education relevant to education based on spiritual and moral values with the humanist approach to develop a critical educational model of participatory education that frees the perpetrator of dehumanization. Therefore, it negates the concept of modern education patterned positivistic but still appreciate the professional education management by exploiting technological progress.